2015
DOI: 10.1209/0295-5075/110/58003
|View full text |Cite
|
Sign up to set email alerts
|

Is poker a skill game? New insights from statistical physics

Abstract: During last years poker has gained a lot of prestige in several countries and, beyond to be one of the most famous card games, it represents a modern challenge for scientists belonging to different communities, spanning from artificial intelligence to physics and from psychology to mathematics.Unlike games like chess, the task of classifying the nature of poker (i.e., as 'skill game' or gambling) seems really hard and it also constitutes a current problem, whose solution has several implications.In general, ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Javarone established poker as a game of skill using tournaments between rational and random agents [20] before introducing population dynamics to enable agents to revise their strategy through play. By employing voter-model-like dynamics, it was shown that under various initial population compositions, the rational strategy is ultimately the one that is learned [27]. Acknowledging that a revision rule predicated on knowledge of the opponent's strategy is unrealistic, most recently Javarone introduced a strategy revision rule that only depends on the payoff received.…”
Section: Previous Workmentioning
confidence: 99%
“…Javarone established poker as a game of skill using tournaments between rational and random agents [20] before introducing population dynamics to enable agents to revise their strategy through play. By employing voter-model-like dynamics, it was shown that under various initial population compositions, the rational strategy is ultimately the one that is learned [27]. Acknowledging that a revision rule predicated on knowledge of the opponent's strategy is unrealistic, most recently Javarone introduced a strategy revision rule that only depends on the payoff received.…”
Section: Previous Workmentioning
confidence: 99%
“…Financial trading [43], emergency medicine [44], and even poker games [45] are just a few examples we can mention to appreciate the relevance of a heterogeneity in risk and reward perception in a system. For instance, rational but risky decisions can be essential to achieve favorable outcomes, and individuals actually show a variety of behaviors in the above listed activities.…”
Section: Introductionmentioning
confidence: 99%
“…Through exhaustive iteration, the game has been weakly solved and optimal strategies obtained for decision making under certain conditions, including for games with only two players [2,13]. Similarly, there has been significant progress looking at the effects of irrational and suboptimal behaviour in poker playing [6,7]. Perhaps the most interesting of these look at neuroevolution models, which are trained on opponents' behaviour on prior hands to predict when certain players might be playing suboptimally [4,8].…”
Section: Introductionmentioning
confidence: 99%